Peningkatan Motivasi Belajar Anak Asuh Melalui Layanan Bimbingan Kelompok di Panti Asuhan Al-Falah Padang - Oki, Sudna Sari; Syukur, Yarmis; Sukma, Dina (Universitas Negeri Padang, 2013)
Learning motivation was considered as a crucial factor for students especially those living in the orphanages. The orphans, certainly, had lack of facilities and attention in learning. The purpose of this research is to know and improve the orphans learning motivation by group guidance service. This was an experimental research which used one group pretest post-test design. The result of the research revealed that there was an improvement on the orphanages’ learning motivation at Panti Asuhan Al-Falah Padang before and after the treatment given.